History and ethnography of Mongolian-speaking peoples in materials of O.M. Kowalewski in library holdings of Vilnius University - Polyanskaya, Oksana N. N. (Acta Orientalia Vilnensia, 2009)
Buryat State University The article is devoted to a famous diary that was written by Orientalist Osip (Józef) Michailovich Kowalewski and is being stored in the script department of the library of Vilnius University. This article is one of the first attempts to introduce it to the scientific field. The document, entitled Diary of Pursuits in 1832, is an important source of the history and ethnography of Mongolian-speaking peoples and is an essential supplement to well-known materials about these peoples.